From noticing challenges to adaptive actions: fostering transitive reflexivity of pre-service GFL teachers through service-learning counseling practices - Lazović, Milica (Frontiers in Education, 2026)
This study investigates how 14 pre-service teachers of German as a foreign language engage in collaborative reflection within team meetings following independent counseling and reflection phases—in a service-learning context and over the course of one semester. Four audio-recorded group reflections are analyzed qualitatively with a focus on two aspects: perceived challenges and self-perceived adaptive practices. The analysis provides a macro-level insight into the collective reflection space for multidimensional concepts, and further reveals the micro-reflexive dynamics in a case study. Adopting a short-term longitudinal perspective, the study further examines how these reflections change across a semester-long advisory cycle. The participants’ perceptions of problems and their self-perceived adaptations are analyzed within the framework of transitive reflection, uncovering a dynamic interplay between different aspects and shifts toward more process-oriented, multidimensional adaptive and co-adaptive orientations. Transitive reflexivity is approached across three interrelated dimensions: novices’ transitions from problem noticing to adaptive actions; domain-specific reflexive shifts over time (transition in problem perception and adaptivity), and the emergence of a transitive orientation that links process understanding with adaptive, discursive, and learning-related dimensions. The study advances the conceptual framework of transitive reflexivity and substantiates its relevance for ongoing and future empirical inquiry in teacher education. The study underscores advisory settings as fertile contexts for cultivating transitional and adaptive professional self-understanding and reflexivity, while acknowledging the interrelation of multidimensional transitive processes in reflection and interaction, in different phases and types of action cycles, as a promising direction for future research.